Emerging Genomic Technologies for Agricultural Biotechnology: Current Trends and Future Prospects - Md. Anowar, Hossain (Frontiers Media S.A., 2023)
Twenty years from now, the earth’s population will need 55% more food than it can currently produce. However, agriculture is facing severe challenges such as global climate change, exhausted resources, reduction of arable lands and various pathogen attacks. Advances in genomic technologies may offer potential solutions to these agricultural problems. Recent years have seen the rapid development of new genomic technologies such as CRISPR, TALENS and ODM (collectively gene editing), as well as doubled haploids, molecular markers and mapping populations. Together with the rapidly expanding availability of genome sequence data, these technologies have the potential to transform plant breeding.